Impact of Market Orientation on Marketing Performance of Convection Businesses - Devi Mariam; Vararillo, Chen; Fatima, Carlos (JMEB Jurnal Manajemen Ekonomi & Bisnis, 2024)
The convection industry plays an important role in a region's economy through job creation, contribution to local income, and support for the development of supporting industries. The industry can also boost exports and tourism if it produces high-quality and innovative products. In the context of intense competition, market orientation is key to understanding consumer needs, market trends, and industry competition. This study aims to explore the impact of market orientation on the marketing performance of convection businesses. The research method used is a quantitative approach with data collection through surveys, observations, and interviews. The results showed that market orientation has a significant positive influence on marketing performance in the convection business. While customer orientation does not have a significant direct influence on marketing performance. Therefore, it is important for convection businesses to focus on market orientation to improve their marketing performance. The combination of strong market orientation and product innovation can help convection businesses strengthen their position in the market and achieve long-term growth.